US Monetary Policy, Global Risk Aversion, and New Zealand Funding Conditions - Eric Tong (New Zealand Government, The Treasury, 2018)
Instrumenting US monetary shocks with fed funds future contracts and extracting global risk sentiment from VIX, this paper uses a structural vector autoregression framework to estimate the causal impact of US monetary policy on New Zealand financial and real sectors. The paper finds that 20 basis points increase in US one-year rate leads to about 14 and 59 percent increase in domestic and external funding spreads of New Zealand banks, respectively. The paper also finds that credit default swap spread rises contemporaneously following a US monetary tightening shock. Similar patterns are documented in Australia, Canada, Sweden and United Kingdom. These results suggest the existence of a global financial cycle underpinned by US monetary policy, and prompt the reassessment of the relevance of Mundellian trilemma in an increasingly globalised economic system.
Keywords: F30; G21; 330; US monetary policy; risk aversion; NZ funding conditions